Green Marketing: The Role of Environmental Knowledge As A Moderating Variable - Purwanto, Edy; AR, M. Munir Syam; Arifin, Miftahol (Yayasan Sinergi Kawula Muda, 2025)
In this era of sophisticated and knowledge-based technology, public awareness of environmental issues has increased significantly throughout the world. Problems related to the environment and its negative impacts are currently a global issue. This research utilizes four dimensions of the green marketing mix, as well as environmental knowledge and purchase intentions. The aim of this research is to analyze the influence of green marketing mix elements, namely product, price, promotion and place, on the purchasing intentions of generation Z consumers in Sumenep. Then, what is the role of environmental knowledge as a moderating variable in the relationship between green marketing mix and purchase intention? The approach used is a quantitative approach. The location of this research was carried out in Sumenep Regency. The objects used in this research are environmentally friendly products. The number of respondents involved in this research was 192 people, who were selected using the purposive sampling method. Data was collected by distributing questionnaires directly to respondents. Hypothesis testing was carried out using multiple linear regression analysis and Hierarchical Moderated Regression (HRM). The research results show that the green product variable does not have a significant influence on consumer purchase intentions. Meanwhile, the green price, green place and green promotion variables partially show a significant positive influence on purchase intention. Testing the moderating effect of environmental knowledge shows that the environmental knowledge variable moderates the influence of green products, green price, and green promotion on purchase intentions, but environmental knowledge does not moderate the influence of green places on consumer purchase intentions.